Respuestas

2012-05-09T16:58:39+02:00

1) x²- 5x+6 = 0

x = 5± 5²-4.6
2


x= 5± 25-24
2

x= 5± 1
2


x1 = 5 - 1 = 4/2 = 2
2


x2 = 5+1 = 6/2 = 3
2

 

2) 2x² - 7x + 3 = 0

x = 7²-4.2.3
4


x = 49-24
4


x = 7± 25
4

x= 7±5
4

x1= 12/4 =3
x2 = 2/4 = 1/2

 

3) -x² + 7x -10 = 0

(-1) (-x²+7x-10) = (-1).0

x² - 7x + 10 = 0


x = 7± 7² - 4.10
2


x = 7± 49-40
2

x = 7±9
2


x = 7±3
2

x1 = 10/2 = 5

x2 = 4/2 = 2

 


4) x² - 2x +1 = 0


x = 2± 2² - 4.1
2

x = 2± 4-4
2


x = 2± 0
2

x = 2±0
2


x = 2/2 = 1


x1 = 2-0 = 2/2 =1
2


x2 = 2+0 = 2/2 = 1
2

lo mismo xD

 


5) x² -4x +4 = 0

x = 4± 16-16
2

x = 4/2

x = 2

 


6 ) 2x-3 = 1- 2x + x²


x² - 4x +4 = 0

x = 4± 16-16
2

x = 4/2 = 2

 

7) x²+(7-x)² = 25


x² + 49 - 14x + x² = 25


x² - 7x + 12 = 0


x = 7± 49-48
2

x = 7±1
2


x1 = 7+1/2 = 4

x2 = 7-1/2 = 3

 

8) 7x²+21x-28 = 25


x²+3x - 4 = 0

x = -3 ± 9+16
2

x = -3 ± 5
2

x1 = (-3) + 5 = 2/2 = 1
2

x2 = (-3)-5 = -8/2 = -4
2


9) -x²+4x - 7 = 0

x² - 4x + 7 = 0

x = 4 ± 16-28
2


x = -3 ± -12
2

Respuesta ; sale - raiz de 12 imaginario


10) 18 = 6x+x(x-13)

18 = 6x+x² - 13x
x² - 7x - 18 = 0

 


x = 7 ± 49+72
2


x = 7 ± 121
2

x = 7± 121
2


x1 = 18/2 = 9

x2 = -4/2 = -2